Preoperative diagnosis of a pulmonary artery sarcoma. Issue 9 (September 1995) - Velebit, V; Christenson, J T; Simonet, F; Maurice, J; Schmuziger, M; Hauser, H; Didier, D
Abstract : A pulmonary artery sarcoma was diagnosed preoperatively by magnetic resonance imaging enhanced with gadolinium and confirmed by percutaneous computed tomographic guided needle biopsy. Accurate preoperative diagnosis allowed planned curative surgery with removal of the right ventricular outflow tract and reconstructive surgery using a cryopreserved homograft.